A comparison of the cataloguing and classification curriculum and job requirements. Issue 6 (13th August 2018) - Sibiya, Philangani Thembinkosi; Shongwe, Mzwandile Muzi
Abstract : Purpose: The purpose of this paper is to compare the cataloguing and classification curriculum offered in South African LIS schools and the job market requirement for cataloguers in South Africa (SA). It was instigated by the changes that have occurred in the LIS field over the past decade, especially in cataloguing and classification. Design/methodology/approach: An interpretive, qualitative approach was used, and content analysis was used as a research and data analysis method. Data were obtained from 3 sources: cataloguing and classification course outlines obtained from 6 LIS schools, 18 interviews conducted with professional cataloguers and 10 job advertisements obtained through newspaper scanning and from the LIASA listserv. Findings: The results indicate that LIS schools teach basic and advanced cataloguing and classification theory and practical topics. The main objective of the courses is to teach students knowledge organisation. The subjects are offered at bachelor's degree and postgraduate diploma levels. Tools such as AACR2, RDA, MARC21, DDC and LCSH are mainly used to teach the courses. Professional cataloguers and job advertisements indicate that employers require the knowledge and skills to use the above-mentioned tools. Job advertisements also indicate that a national diploma and two years' work experience are the minimum requirements for employing cataloguers. Practical implications: This paper will inform academics whether they are teaching the relevant curriculum. If not, they will have to implement changes or improvements to the current curriculum. It will also help employers get a picture of what is offered in LIS schools and make judgements on whether it is relevant in the job market or not. Originality/value: This paper has compared what is offered in LIS schools and what is required in the job market and found that there is match between what is offered and required, although there are areas to be improved. This is the first paper to establish that link in SA.